PENDAMPINGAN PEMASARAN DIGITAL MARKETING BAGI KELOMPOK PKK DESA GEBANGANOM - Risqi, Saiful; Oktaviani, Sintia; Huda, Dani Miftahul; Hisyam, Fawaz Nur; Sugiharto, Prasetyawan Aji; Santoso, Yan Imam; Najib, Muhammad Reza Ainun (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Digital Marketing Assistance for the Gebanganom Village PKK Group aims to increase the economic potential of group members through the use of digital technology. With the increasing public need for products and services that can be easily accessed, this training is expected to help PKK members who number 25 people, the majority of whom are women, in optimizing their businesses. Although there have been several members who run independent businesses, the lack of knowledge and skills in digital marketing is the main challenge. The program includes training and mentoring in digital marketing strategies, including the use of social media and e-commerce platforms, to expand consumer networks and increase product sales. The results of the training showed that participants gained a better understanding of branding and digital marketing, as well as being able to plan products that fit market needs. Through collaboration between various parties, it is hoped that the Gebanganom Village PKK group can contribute to improving the overall village economy and improving the welfare of the local community